(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The Agricultural Regionalization is a very important fact to the farmers help in taking decision for crop cultivation and this may be done with the help of different methods like Crop Combination, Crop Concentration, and Patterns of Crop Rotation etc. The Study identifies the basic crop combination in Junnar tahsil, which basically an agriculture dominated area. Normally crops are grown in a Combination rather than single. The present study is based upon the secondary data collected from Agriculture Department of Pune District and the Method has been adopted to calculate the value belongs to Wever’s Method. The calculation of the crop combination was done for 181 villages for the year 2018-19, using Weaver’s method. The crop combination of the Junnar tahsil has shown a spatial variation of crop diversity and pattern, In the present study, on the basis of the calculation of the crop combination of the Junnar tahsil, we have found four types of crop combination i.e. two crop combination, three crop combination, four crop combination, and five crop combination